Pendugaan Umur Simpan Sambal Gami Dikemas dalam Jar Polyethylene Terephthalate (PET) - Ina Siti Nurminabari; Sumartini Sumartini; Nadyne Kusumah (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2022)
“Sambal gami” is a typical sauce from Bontang, East Kalimantan, but there has been no research estimating its shelf life. This study aimed to determine the rate of deterioration and estimate the shelf life of “sambal gami” using the Accelerated Shelf Life Testing method based on the Arrhenius approach. “Sambal” was packaged in a Polyethylene Terephthalate plastic jar and stored at 25°C, 30°C and 40°C. Parameters observed during storage Free Fatty Acid (FFA) levels and the number of microbes. The results showed the smallest activation energy value to activate the shelf life of sambal gami, the parameter of FFA levels, namely in the zero-order reaction with linear regression y = 0.3404x + 1.5304, R2 value = 0.9796, quality constant of 0.336 and has shelf life of 6 days at 25°C. Based on the parameters of the total number of microbes that occur in the first-order reaction, with linear regression y = 0.2491x + 7.9356, R2 value = 0.9854, the quality degradation constant is 0.263 and has a shelf life of 5 days at 25°C. The headspace obtained on the package is 40.8%. An excellent standard index for headspace is 10% of pack height.